A COMPARATIVE STUDY OF FEMALE TEACHER TRAINEES PURSUING INTEGRATED COURSES IN ARTS AND SCIENCE STREAM IN RELATION TO THEIR ACADEMIC RESILIENCE AND LOCUS OF CONTROL - Sharma, Pragati; Trivedi, Lavleena (ShodhKosh: Journal of Visual and Performing Arts, 2024)
"विद्या ददाति विनयं विनयाद्याति पात्रताम्। पात्रत्वाद्धनमाप्नोति धनाद्धर्मं ततः सुखम्॥" (Knowledge gives humility, humility leads to worthiness, Worthiness brings wealth, wealth fosters righteousness, and righteousness brings happiness.).